Different but the Same: Negotiation of Personhoods and Christianities in Western Amazonia - Opas, Minna (fi=Turun yliopisto|en=University of Turku|, 2008)
Electronic version of Minna Opas's doctoral thesis which originally came out in print format in November 2008. Electronic version was published in April 2023.